ANALISA KEMAMPUAN HANTAR ARUS PADA KABEL NYY DENGAN MENGGUNAKAN RAK KABEL TERTUTUP - Irvan Buchari Tamam; Andi Makkulau; Dessy Roesdynasari (Sekolah Tinggi Teknik - PLN, 2015)
Cable conditions of different loads, both medium and high, can be deployed on open or closed wiring racks. On the open cable rack is not trapped, but on the cable rack closed strongly conducting cable current is strongly influenced air. This is because inside the closed cable rack itself between the mass surface of the cable and the lid of the rack there is trapped air. This trapped air is a heat insulation that can affect the heat energy of the cable mass so it is not easy to flow into the surrounding air. Temperature increases in the mass of cables with different cable loads will affect the current carrying strength of the cables. Based on the above problems it is necessary to review the effect of load diversity on the current carrying strength of cables, especially on the closed cable rack and environmental temperature factors outside the cable. From the results of the research it is found that the more number of high-loaded cables NYY (Heavily Loaded cables) then the current carrying strength decreases. But the greater the diameter of the cable then the conductivity of the current will be greater. This is indicated by the average increase for the cable NYY with diameter 16 mm2, 25 mm2 and 50 mm2of 17.97 A.